2007
DOI: 10.1002/etep.189
|View full text |Cite
|
Sign up to set email alerts
|

Surface degradation of styrene acrylonitrile exposed to corona discharge

Abstract: SUMMARYAn experimental investigation of the degradation of styrene acrylonitrile (SAN) exposed to corona discharge under ambient conditions was presented. SAN specimens were subjected to a corona stress generated by two plane parallel electrodes. The surface physicochemical changes were studied using scanning electron microscope, energy-dispersive X-ray analysis, Fourier transformed infrared spectroscopy and surface resistance measurements.The results showed significant damage on the specimen' surface caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The work of Moudoud and others [30] showed that the electrical ageing induces a change in the polymethyl methacrylate color. In the work concerning the styrene acrylonitrile surface degradation exposed to corona discharge, Handala and Lamrous [31] observed a change in the material appearance. They indicated that these evolutions are due to oxidation or functional group elimination along the polymer chain.…”
Section: Termination Stepmentioning
confidence: 99%
“…The work of Moudoud and others [30] showed that the electrical ageing induces a change in the polymethyl methacrylate color. In the work concerning the styrene acrylonitrile surface degradation exposed to corona discharge, Handala and Lamrous [31] observed a change in the material appearance. They indicated that these evolutions are due to oxidation or functional group elimination along the polymer chain.…”
Section: Termination Stepmentioning
confidence: 99%
“…Several works focused on the study of the electric breakdown phenomenon of insulating materials and its corresponding driving force have been reported [1,3,[5][6][7][8][9][10][11][12][13][14]. Electric breakdown occurs when the current flowing through the sample increases, leading to its failure and consequently, the applied voltage cannot be stable.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the impacts of long-term corona discharges on the hydrophobicity characteristics of composite insulator surface as well as on the ageing involved, different artificial corona ageing tests [1,5,10,15,16,[23][24][25][26][27][28][29][30][31][32] have been developed, so as to avoid the randomness of distribution and uncontrollability of the discharge intensity. The work carried out internationally and concentrating on investigations of the "polymer-corona" system in high voltage outdoor applications has been summarized in our former paper [33].…”
Section: Introductionmentioning
confidence: 99%